Pengaruh Kode Etik terhadap Perilaku Profesional Akuntan dan Kualitas Laporan Keuangan - Trenda Indri Ardianti; Siti Nur Azizah; Tries Ellia Sandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effect of the professional code of ethics on accountants’ professional behavior and the quality of financial statements. The credibility of financial information largely depends on ethical conduct and professional responsibility in accounting practices. Using a quantitative associative approach, this research analyzes how ethical principles shape professional behavior and how such behavior contributes to the reliability, transparency, and compliance of financial reporting. The findings indicate that a strong understanding and consistent application of the code of ethics significantly influence accountants’ professional behavior, particularly in maintaining integrity, independence, and objectivity. Furthermore, professional behavior acts as a mediating variable that strengthens the relationship between the code of ethics and financial statement quality. Accountants who demonstrate high ethical awareness tend to produce financial reports that are more reliable and aligned with applicable accounting standards. This study highlights that ethical values are not merely formal guidelines but essential foundations for professional conduct and high-quality financial reporting. The results provide practical implications for accounting professionals, organizations, and professional bodies in strengthening ethical education and enforcement to enhance public trust in financial information.